2012
DOI: 10.1242/jcs.105114
|View full text |Cite
|
Sign up to set email alerts
|

VPS13Regulates Membrane Morphogenesis During Sporulation inSaccharomyces cerevisiae

Abstract: SummaryThe hereditary disorders chorea acanthocytosis and Cohen syndrome are caused by mutations in different members of a family of genes that are orthologs of yeast VPS13. In vegetatively growing yeast, VPS13 is involved in the delivery of proteins to the vacuole. During sporulation, VPS13 is important for formation of the prospore membrane that encapsulates the daughter nuclei to give rise to spores. We report that VPS13 is required for multiple aspects of prospore membrane morphogenesis. VPS13 (1) promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(162 citation statements)
references
References 57 publications
5
150
1
Order By: Relevance
“…In this context, it has been proposed that the yeast Atg18/Atg2 complex is required to generate negative curvature at the forming autophagosome or fulfi lls an essential function at the elongating tips of the phagophore ( 43 ). Likewise it was recently found that Vps13 regulates membrane bending and promotes the expansion of the prospore membrane in yeast ( 68 ). From this, one would assume that malfunctions of either of the human Atg2/Vps13 proteins should be correlated to distinct human pathologies with defects in intracellular membrane biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been proposed that the yeast Atg18/Atg2 complex is required to generate negative curvature at the forming autophagosome or fulfi lls an essential function at the elongating tips of the phagophore ( 43 ). Likewise it was recently found that Vps13 regulates membrane bending and promotes the expansion of the prospore membrane in yeast ( 68 ). From this, one would assume that malfunctions of either of the human Atg2/Vps13 proteins should be correlated to distinct human pathologies with defects in intracellular membrane biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after loss of Vps13p function an in increased cytotoxicity of an expanded polyQ domain in Rnq1p has been detected (10). Recently, Vps13p was shown to be required for prospore membrane morphogenesis through regulation of phosphatidylinositol phosphatases (11,12). Our previous results have established the 450 kDa protein COH1 as an atypical Golgi matrix protein lacking coiled-coil domains that is crucial for Golgi complex organization.…”
mentioning
confidence: 82%
“…24,25 In simpler organisms, null mutants in Saccharomyces cerevisiae and Tetrahymena thermophila suggest a role of Vps13 and VPS13A in membrane traffic and phagocytosis respectively but the precise VPS13 function is largely unknown. [26][27][28] Here we describe that the VPS13-related protein TipC is required for efficient autophagy in D. discoideum. We extended our observations to human VPS13A by analyzing autophagy in RNA-interfered HeLa cells.…”
Section: Introductionmentioning
confidence: 90%